DNA hypermethylation of extracellular matrix‐related genes in human periodontal fibroblasts induced by stimulation for a prolonged period with lipopolysaccharide derived from Porphyromonas gingivalis. (9th November 2015) - Takai, R.; Uehara, O.; Harada, F.; Utsunomiya, M.; Chujo, T.; Yoshida, K.; Sato, J.; Nishimura, M.; Chiba, I.; Abiko, Y.
Abstract : Objectives and Background: The involvement of DNA methylation in periodontal disease is not clear. Lipopolysaccharide (LPS) derived from Porphyromonas gingivalis is involved in the progression of periodontal disease. We recently developed an in vitro model of LPS infection in human periodontal fibroblast cells (HPdLFs) for a prolonged period. In this study, we examined genome‐wide analysis of DNA methylation in HPdLFs stimulated with LPS derived from P. gingivalis for a prolonged period. We noted the hypermethylation of extracellular matrix (ECM)‐related genes and examined whether hypermethylation affected their transcription levels. Material and Methods: HPdLFs were grown in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum. The culture was repeated, alternating 3 d with LPS derived from P. gingivalis and 3 d without LPS for 1 mo. Untreated samples were used as controls. DNA was analyzed using the human CpG island microarray. Quantitative methylation‐specific polymerase chain reaction was carried out to confirm reproducibility of the microarray data. The expression levels of mRNA of the selected ECM‐related genes from the data were analyzed by quantitative reverse transcription–polymerase chain reaction. Results: We found 25 ECM‐related genes with hypermethylation at the CpG island of the promoter region, which exhibited a fourfold greater hypermethylation than controls. Among these genes, hypermethylation of nine ECM‐related genes, FANK1, COL4A1‐A2, 12A1 and 15A1, LAMA5 and B1, MMP25, POMT1 and EMILIN3, induced a significantly downregulated expression of their mRNA. Conclusion: These results indicate that LPS derived from P. gingivalis may cause DNA hypermethylation of some ECM‐related genes followed by downregulated expression of their transcriptional levels.